Perceptions of "Tinuktuk" The Traditional Food The Simalungun Ethnic, North Sumatra - Tarigan, Novriani (Jurnal Health Sains, 2024)
In the Simalungun Batak community, known and commonly consumed is Tinuktuk. Tinuktuk is a local Simalungun cultural heritage that is usually given to Simalungun women who have just given birth so that they are strong and able to care for their babies and provide optimal breastfeeding. This study aims to determine the public's perception of tinuktuk. The data collection method is divided into two, namely the online method using social media researchers and the direct method carried out in 3 villages in Simalungun Regency. The results obtained showed that more than half of the respondents obtained tinuktuk by buying it, consuming tinuktuk in the form of chili sauce or mixing it with soup. That tinuktuk makes the body warm and fresh, shows that the combination of ingredients for tinuktuk synergistically functions as an antioxidant. Of the 10 questions regarding perceptions of tinuktuk, 80% of respondents agreed. Tinuktuk needs to be popularized and developed in a practical form to be consumed at any time. Further studies are needed on the bioactive compounds contained in tinuktuk.